An Analysis of Lexical and Contextual Meaning on Sport News in Jawa Pos Newspaper (Linguistics Study) - Theresia Budi Sucihati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
Semantic is the branches of linguistics. This researh is about linguistics which analyse about lexical meaning and contextual meaning. By reading of the news article, we can get knowledge about appreciates literature and the background of the language. Therefore, the researcher interested in analyzing the lexical and contextual meaning used in sport article. The researcher dedicated to give the title of this research “An Analysis of Lexical and Contextual meaning on Sport News in Jawa Pos Newspaper”. The problem of this study are: (1) How is lexical meaning used on sport news in Jawa Pos newspaper? (2) How is contextual meaning on sport news in Jawa Pos newspaper? The researcher takes some newspaper edition in of February 2018. This study uses a descriptive qualitative method because the researcher would analysze and interpret the object research of sport article. The step to obtain the data is by collecting sources of the data from sport article in Jawa Pos newspaper. After that selects the sport article and understand the content of the article, the researcher conducts and analyzes the data the last is make conclusion. The result of this research is as follows: (1) every word of lexical meaning used in sports articles aims to attract news readers or newspapers, while (2) every word of lexical meaning can be analyzed using contextual meaning so that the reader can understand the content of the news. The researcher expects this research will be useful for the other researchers who are eager to know more about semantics. Moreover, semantic is an important branch of linguistics that is interesting to be studied, especially when it is applied to literary works, such us news, novel or poem etc.